Study on the Mechanism of Failure in the LiF–NaF–KF Molten-Salt-Purifying Processing System - Liu, Huajian; Chen, Shuangjian; Fu, Jie; Yang, Xinmei; Tang, Rui; Ge, Min; Wang, Jianqiang; Zhou, Xingtai; Xie, Leidong (Frontiers in Materials, 2022)
The failure of LiF–NaF–KF molten salt processing engineering was investigated. The results indicate that the failure is related to the blockage of pipes. The mechanism of blockage was studied systemically. The results reveal that the blockage of pipes was attributed to corrosion. UNS 022N01 alloy vessel was corroded in molten salt to form KNiF3 and K2NiF4. The corrosion products were reduced by H2 to form metallic Ni, which is the precipitant in salt. The transfer of precipitant in terminal salt was stopped by incomplete root penetration, which results in one pipe blocked at the welded joint. The corrosion products were reduced by H2 to form metallic Ni and deposited on the inner surface of H2 gas outlet, which resulted in another blocked pipe.